The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1590/2358-2936e2020038
|View full text |Cite
|
Sign up to set email alerts
|

Do the day/night periods and tidal cycles modulate the abundance and distribution of Callinectes danae Smith, 1869 (Brachyura, Portunidae) in an estuary-bay complex from southeastern Brazil?

Abstract: Do the day/night periods and tidal cycles modulate the abundance and distribution of Callinectes danae Smith, 1869 (Brachyura, Portunidae) in an estuary-bay complex from southeastern Brazil?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The number of fishers sampled varied according to the fishers' activity and logistical survey constraints. Only nocturnal fishing trips were sampled to ensure a similar, high catchability of macroinvertebrates that are usually more active at night than at day (Pescinelli et al, 2020). This decision was supported by the fact that we observed that trawl net fishing was mostly nocturnal in the survey area.…”
Section: Characterization Of Benthic Macroinvertebrate Catchesmentioning
confidence: 99%
“…The number of fishers sampled varied according to the fishers' activity and logistical survey constraints. Only nocturnal fishing trips were sampled to ensure a similar, high catchability of macroinvertebrates that are usually more active at night than at day (Pescinelli et al, 2020). This decision was supported by the fact that we observed that trawl net fishing was mostly nocturnal in the survey area.…”
Section: Characterization Of Benthic Macroinvertebrate Catchesmentioning
confidence: 99%